Particulate multivalent presentation of the receptor binding domain induces protective immune responses against MERS-CoV. Issue 1 (1st January 2020) - Okba, Nisreen M. A.; Widjaja, Ivy; van Dieren, Brenda; Aebischer, Andrea; van Amerongen, Geert; de Waal, Leon; Stittelaar, Koert J.; Schipper, Debby; Martina, Byron; van den Brand, Judith M. A.; Beer, Martin; Bosch, Berend-Jan; et al.
ABSTRACT: Middle East respiratory syndrome coronavirus (MERS-CoV) is a WHO priority pathogen for which vaccines are urgently needed. Using an immune-focusing approach, we created self-assembling particles multivalently displaying critical regions of the MERS-CoV spike protein ─fusion peptide, heptad repeat 2, and receptor binding domain (RBD) ─ and tested their immunogenicity and protective capacity in rabbits. Using a "plug-and-display" SpyTag/SpyCatcher system, we coupled RBD to lumazine synthase (LS) particles producing multimeric RBD-presenting particles (RBD-LS). RBD-LS vaccination induced antibody responses of high magnitude and quality (avidity, MERS-CoV neutralizing capacity, and mucosal immunity) with cross-clade neutralization. The antibody responses were associated with blocking viral replication and upper and lower respiratory tract protection against MERS-CoV infection in rabbits. This arrayed multivalent presentation of the viral RBD using the antigen-SpyTag/LS-SpyCatcher is a promising MERS-CoV vaccine candidate and this platform may be applied for the rapid development of vaccines against other emerging viruses such as SARS-CoV-2.